2014
DOI: 10.1002/pamm.201410059
|View full text |Cite
|
Sign up to set email alerts
|

Phase Field Approximation of Dynamic Brittle Fracture

Abstract: The numerical assessment of fracture has gained importance in fields like the safety analysis of technical structures or the hydraulic fracturing process. The modelling technique discussed in this work is the phase field method which introduces an additional scalar field. The smooth phase field distinguishes broken from undamaged material and thus describes cracks in a continuum. The model consists of two coupled partial differential equations -the equation of motion including the constitutive behaviour of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 3 publications
2
19
0
Order By: Relevance
“…In this work, a phase field fracture model based on the generalized Griffith's theory is adopted to simulate the crack initiation and propagation for brittle materials [e.g., Kuhn and Müller , ; Borden et al ., ; Hofacker and Miehe , ; Verhoosel and Borst , ; Schlüter et al ., ; Heister et al ., ]. Since the phase field fracture model employs an implicit function instead of strong discontinuities to represent cracks, it does not require complicated numerical treatments such as generation of enrichment functions [ Dolbow et al ., ], dynamic insertion of cohesive elements [ Zhang and Paulino , ], or modification of the mesh [ Mota et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…In this work, a phase field fracture model based on the generalized Griffith's theory is adopted to simulate the crack initiation and propagation for brittle materials [e.g., Kuhn and Müller , ; Borden et al ., ; Hofacker and Miehe , ; Verhoosel and Borst , ; Schlüter et al ., ; Heister et al ., ]. Since the phase field fracture model employs an implicit function instead of strong discontinuities to represent cracks, it does not require complicated numerical treatments such as generation of enrichment functions [ Dolbow et al ., ], dynamic insertion of cohesive elements [ Zhang and Paulino , ], or modification of the mesh [ Mota et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…Over the past decade, this approach was applied to many areas including elastic fracture [18,17,16], thermoelastic fracture [43,21], thin-film fracture [42,41,45], thin-shells [6], electro-mechanical fracture [1,2], or dynamic fracture [40,20,15,57] to name a few. A major difficulty associated with the variational approach to fracture is the reliance on global energy minimization, which can sometimes result in unrealistic crack paths by making equally admissible "near" and "far" points in configuration space.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, describing these features is still under development for the phase‐field method. May et al, Strobl and Seelig, Schlüter, and Steinke and Kaliske have shown, that the well‐known volumetric‐deviatoric split (V‐D) and spectral split approaches with tension/compression decomposition lead to misleading predictions for the force transfer through the crack. They have proposed and developed a model for the crack kinematics in case of isotropic, linear elastic material.…”
Section: Introductionmentioning
confidence: 99%